1996
DOI: 10.1073/pnas.93.11.5407
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of photoreceptor cGMP phosphodiesterase inhibition by its gamma-subunits.

Abstract: ABSTRACTcGMP phosphodiesterase (PDE) is the key effector enzyme of vertebrate photoreceptor cells that regulates the level of the second messenger, cGMP. PDE consists of catalytic a and 13 subunits (Pa and PIS) and two inhibitory 'y subunits (Py) that block PDE activity in the dark. The major inhibitory region has been localized to the C terminus of Py. The last C-terminal residues -IleIle form an important hydrophobic domain critical for the inhibition of PDE activity. In this study, mutants of Py were design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
72
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 35 publications
3
72
0
Order By: Relevance
“…Although the last few C-terminal residues of P␥ have been reported to physically interact with the catalytic domain to block catalysis (9,(13)(14)(15)(16)(17), the shortest peptide we tested (P␥81-87) showed no ability to inhibit the catalytic activity of PDE6 under our experimental conditions (IC 50 Ͼ 2 mM; Fig. 2).…”
Section: The Last 10 Amino Acids Of P␥ Are Sufficient To Fully Inhibitmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the last few C-terminal residues of P␥ have been reported to physically interact with the catalytic domain to block catalysis (9,(13)(14)(15)(16)(17), the shortest peptide we tested (P␥81-87) showed no ability to inhibit the catalytic activity of PDE6 under our experimental conditions (IC 50 Ͼ 2 mM; Fig. 2).…”
Section: The Last 10 Amino Acids Of P␥ Are Sufficient To Fully Inhibitmentioning
confidence: 99%
“…For example, C-terminally truncated P␥ mutants lacking the last 5-10 amino acids have been reported to result in no inhibition (9,22,23) up to 50% inhibition (15) of catalytic activity. There are also reports that inhibition of PDE6 catalysis can occur without an absolute requirement of the extreme C-terminal amino acids (8,(15)(16)(17).The kinetic mechanism of P␥ inhibition of PDE6 catalysis is generally believed to occur by a simple competition of P␥ and substrate for access to the active site. Although this model is supported by kinetic studies showing competition between cAMP hydrolysis and P␥ binding at the active site (12), similar * This work was supported, in whole or in part, by National Institutes of Health Grant EY-05798.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Both of these P␥ domains bind to P␣␤, allowing effective inhibition of PDE activity by the P␥ C terminus. Initial studies indicated that the major sites of P␣ and P␤ interaction with P␥ are different and located in the N-terminal regions (P␣, 16 -30 and 78 -90; P␤, 91-110 and 211-230) in areas with a high level of dissimilarity between catalytic subunits .More recently, using a cross-linking approach we have demonstrated that the C terminus of P␥ interacts with region P␣-751-763 located within the PDE catalytic domain (Artemyev et al, 1996). In this study, to identify a P␣ region for binding to P␥-24 -45, we have expressed several large domains of P␣ as GST fusion proteins in Escherichia coli.…”
mentioning
confidence: 95%